RNA POLYMERASE GENE BASED RT-PCR ASSAY WITH PRIMERS UPDATE FOR GENUS SPECIFIC DETECTION OF PICOBIRNAVIRUSES - Y. S. Malik; A. K. Sharma; K. Sharma; S. Sircar; K. Dhama (Journal of Animal and Plant Sciences, 2017)
Picobirnavirus (PBV) is an emerging causal agent of gastrointestinal and respiratory infections in humans and animals. Herein, a RNA polymerase gene based RT-PCR diagnostic assay was developed for initial detection of PBVs viral RNA in stool samples. Furthermore, sensitivity, specificity and validation of this assay were accomplished using field samples. The ORF2 (RdRp) coding region was chosen as the target, with more consensus portions within genus in the family Picobirnaviridae, tested in the genogroups I and II (GGI and GGII) of the virus. The RdRp nucleotide sequences from human and animal PBVs were retrieved from the NCBI database (http://www.ncbi.nlm.nih.gov) for primer designing. In this study, a total of 54 stool samples from animals (cattle calves (n=27), piglets (14) and goat kids (13)) suffering with diarrhea were screened. Expected size PCR amplicon of 275 bp was seen in 14 cattle calves, 12 piglets and 3 goat kids. The field validation of RT-PCR assay revealed presence of PBV viral RNA in 53.7% samples (29/54). The described genus specific assay could be applied for the primary detection of PBV infection in animals and, in combination with the genogroup specific PCRs, for the confirmation of new and emerging PBVs in animals.
Keywords: Picobirnavirus; RdRp gene; RT-PCR; New primers; Sensitivity; Specificity; Genogroups